New structural study and reinterpretation of the vibrational spectra of the μ-N,O-hyponitrite bis[pentaamminecobalt(III)]4+ cation - Chacón Villalba, M. E. (2006)
The [(NH3)5CoN(O)NOCo(NH3)5]Br2(NO3)2 Æ 2.5H2O salt was studied by X-ray diffraction methods. Such structural study confirmed the already reported binuclear, bridged structure of the complex cation and allowed a description of the main features of the lattice structure. An infrared and Raman study of that compound was also performed in order to revise the assignments of the vibrational features. Such spectroscopic study, aided by 14/15N replacement and quantum chemistry calculations, permitted a reassignment of the spectral bands originated in the hyponitrite bridge.